Chiral Recognition in Separation Methods Mechanisms and Applications - Berthod, Alain; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
The importance of chiral interactions for both preparative and analytical separations, particularly for pharmaceutical applications, is underlined by numerous publications in this field. Here, for the first time, a team of experienced analysts from industry and academe presents a comprehensive review of the various mechanisms that result in enantiomer separations. A better understanding of these processes is crucial for setting as well as improving chiral separation procedures and also for developing new applications. The coverage in this book includes a range of separation methods, such as gas, liquid, or countercurrent chromatography, and capillary electrophoresis. The special case of chiral ionic liquids is examined in detail. Most modern chiral selectors are discussed, including derivatized polysaccharide- and cyclodextrin-based selectors, along with a newly introduced class of carbohydrates: the cyclofructose selectors. This publication will be required reading not only for research and development departments in the pharmaceutical and cosmetic industries, but also for researchers in toxicology, environmental monitoring, and food research.
Chiral Recognition Mechanisms in Enantiomers Separations: A General View -- Preparation and Chiral Recognition of Polysaccharide-Based Selectors -- Description and Evaluation of Chiral Interactive Sites on Bonded Cyclodextrin Stationary Phases for Liquid Chromatography -- Cyclofructans, a New Class of Chiral Stationary Phases -- Chiral Recognition and Enantioseparation Mechanisms in Capillary Electrokinetic Chromatography -- Chiral Recognition Mechanism: Practical Considerations for Pharmaceutical Analysis of Chiral Compounds -- Chiral Recognition with Macrocyclic Glycopeptides: Mechanisms and Applications -- Vancomycin Molecular Interactions: Antibiotic and Enantioselective Mechanisms -- Enantioselective Recognition in Solution: The Case of Countercurrent Chromatography -- Enantioselective Properties of Nucleic Acid Aptamer Molecular Recognition Elements -- Chiral Ionic Liquids in Chromatographic Separation and Spectroscopic Discrimination.
Keywords: Chemistry; Toxicology; Chromatography; Food science; Pharmacy; Chemistry; Chromatography; Pharmacy; Pharmacology/Toxicology.; Food Science; Environmental Monitoring/Analysis.